Antimicrobial activity of homemade WHO ethanol-based hand rub solution in pediatric department, Dr. Cipto Mangunkusumo National Referral Hospital - Nina Dwi Putri; Hindra Irawan Satari; Mulya Rahma Karyanti; Ari Prayitno; Pratama Wicaksana; Anis Karuniawati; Delly Chipta Lestari; Nabila Maudy Salma; Shindy Claudya Aprianti; Amalia Almira; Andi Annisa Rusyda Khafiyani (Indonesian Pediatric Society, 2022)
Background Hand hygiene is essential in reducing healthcare-associated infections. Alcohol-based hand rub solutions have been reported to have superior antimicrobial efficacy on both bacteria and lipophilic viruses compared to washing with hand soap. In low- and middle-income countries, the cost of infection control poses a challenge. Our hospital produced an ethanol-based hand rub based on a WHO formulation to reduce the infection prevention costs. Objectives To identify the antimicrobial activity of a WHO ethanol-based hand rub solution against bacterial contamination on the hands of healthcare workers at the Department of Child Health, Dr. Cipto Mangunkusumo National Referral Hospital. Methods This cross-sectional study was performed on the hands of healthcare workers (physicians and nurses) working in the Department of Child Health, Dr. Cipto Mangunkusumo National Referral Hospital, Jakarta. A total of 225 specimens from 75 subjects were obtained by collecting swabs on both hands before and after participants worked in the Department of Child Health, Dr. Cipto Mangunkusumo General Hospital. Bacterial culture tests were performed to identify gram-positive and gram-negative bacteria. Bacteria were grouped into no-growth/Bacillus sp, Enterobacteriaceae, cocci, and non-fermenter groups. Results The use of our WHO ethanol-based hand rub solution, generally resulted in a statistically significant decrease in bacterial growth from 84 to 54.6%, before compared to after the hand rub was performed. In more detail, there was a 72.7% decrease in Enterobacteriaceae, a 71.4% decrease in non-fermenters, an 8.6% decrease in cocci and a 44.1% increase in the number of specimens showing no growth bacteria/Bacillus sp. Conclusion Our WHO ethanol-based hand rub has significant antimicrobial activity for common nosocomial pathogens (e.g., Staphylococcus aureus, P. aeruginosa, and K. pneumoniae).